TNF-α mRNA expression as a shared molecular marker in primary hyperparathyroidism and systemic lupus erythematosus: a new perspective on osteoimmunology - Nearmeen M. Rashad; Lobna I. Kotb; Nahawand A. El-Deeb; Mai Mahmoud Mohamed El-Daly; Rehab M. Atef; Lamiaa Goda Mohammad; Ahmed El-Sayed Hassan; Amira M. Elsayed (The Egyptian Journal of Internal Medicine)
Abstract Background Tumor necrosis factor-α (TNF-α) is an immune regulator, involved in the pathogenesis of numerous diseases, such as systemic lupus erythematosus (SLE). Primary hyperparathyroidism (PHPT) is an endocrinopathy recognized by the hypersecretion of parathormone. Despite the increasing evidence of immune derangement in parathyroid disorders, results are still inconsistent. We aimed to examine TNF-α mRNA and serum levels in SLE with and without PHPT to elucidate the immunomodulatory and pathogenic roles of TNF-α mRNA and serum in both diseases. We recruited 70 patients and 70 age-and sex-matched controls. Diagnosis of PHPT and SLE was based on a combination of immunological markers, clinical symptoms, biochemical tests, imaging, and parathyroid scintigraphy. We evaluated serum levels of TNF-α using ELISA and the expression of TNF-α mRNA in peripheral blood using real-time PCR. Results TNF-α serum and mRNA relative expression values were overexpressed in SLE group with PHPT (28.25 ± 10.9, 6.31 ± 3.1, respectively) in comparison to SLE group without PHPT (19.09 ± 7.21,4.02 ± 1.9, respectively) and control group (3.6 ± 1.668, 0.91 ± 0.16, respectively), (P < 0.001*). TNF-α mRNA and serum levels were significantly positively correlated with SLEDAI, ESR, alkaline phosphatase, iPTH, adjusted calcium, ionized calcium, and 24-h urine for calcium. Linear regression tests revealed that serum TNF-α, ESR, and iPTH were the only predictors among other parameters studied, (P < 0.001*). Concerning TNF-α mRNA, adjusted calcium was the only predictor among other parameters studied, (P < 0.001*). Conclusions TNF-α mRNA and serum levels are elevated in SLE, particularly in patients with PHPT. Intriguingly, they were significantly correlated to markers of lupus activity and bone resorption.